(untitled) (Research, Society and Development, 2023)
The city of Fortaleza has its history and development intimately linked to migration processes coming from towns within the countryside. In this context, this research deepens in the notions of collective memory, city and identity, seeking to elucidate how collective memory affects the process of building an identity linked to the city of Fortaleza among subjects from country town´s origin. For this purpose, the Theory of Social Representations is the key to understanding the studied phenomenon and makes use of life history interview techniques in combination with exploratory questions, having the interpretation of meanings as a guide for the analysis of the collected material. The research results indicates the influence of collective memory on the establishment of identity links with Fortaleza among subjects of country town´s origin acting through social groups that maintain a common collective memory from the countryside town. The union of these groups in the city space favors the transmission and maintenance of such collective memory that provides a greater identification with the country town of origin to the detriment of the construction of an identity linked to Fortaleza.